Effective Leadership and Cultural Diversity Management in Multinational Corporations - Nurwati, Nurwati; Gani, Abdul; Berliani, Ainun (Journal Development Manecos, 2024)
This study examines the management of organizational culture in multinational corporations (MNCs), focusing on the impact of cultural diversity, communication strategies, and leadership on organizational performance. Using a quantitative research approach, data were collected from 450 employees across various MNCs through structured surveys. The analysis employed correlation, regression, and ANOVA to assess the relationships between cultural integration, communication effectiveness, leadership, and organizational outcomes. Findings reveal that effective management of cultural diversity, through culturally intelligent leadership and tailored communication strategies, significantly enhances organizational performance and employee engagement. The results highlight the challenges MNCs face in balancing global corporate values with local cultural nuances, emphasizing the need for leadership that is adaptable and sensitive to diverse cultural contexts. This study addresses gaps in the literature by providing empirical evidence on the role of leadership and communication in fostering cohesion and alignment within global operations. It also underscores the importance of cross-cultural training and development programs to reduce conflicts and promote collaboration. These findings contribute to the growing discourse on organizational culture management in the global business environment, offering practical implications for MNCs in managing diverse teams across regions.